Penerapan Solution-Focus Brief Counseling (SFBC) Untuk Meningkatkan Kemampuan Kerjasama Pada Mahasiswa - Atika, Amelia; Hastiani, Hastiani (Nusantara of Research : Jurnal Hasil-hasil Penelitian Universitas Nusantara PGRI Kediri, 2022)
The research aims to produce a solution focus brief counseling (SFBC) guide to improve the cooperative ability of guidance and counseling students. The focus of the problem in this research is to improve the cooperation ability of IKIP-PGRI Pontianak students. The approach uses Classroom Action Research (CAR) through two cycles. Assessment of student collaboration aspects in applying SFBC guidelines to improve student collaboration skills. Assessment of aspects of student cooperation in implementing the SFBC guide uses observation guidelines while indicators include communication, coordination, contribution, tolerance, responsibility, and motivation. The results showed that the SFBC guide could improve students' collaboration skills. The acquisition of cooperation indicators in each cycle is classified as "Good" and "Very Good" for the average acquisition of each cycle. SFBC guidelines to improve student collaboration skills consist of Rationale, implementation objectives, implementation, SFBC therapy techniques, evaluation, and follow-up. After implementing the SFBC guidelines, it can be concluded that the SFBC guidelines can be used to improve student collaboration skills.